Analisis dan Evaluasi Peraturan Pemerintah No. 71 Tahun 2019 tentang Penyelenggaraan Sistem dan Transaksi Elektronik (PSTE) dalam Menanggulangi Kejahatan Ransomware di Indonesia - Afriqil Wildan; Samsul Arifin (Academos, 2025)
This study analyzes and evaluates the effectiveness of Government Regulation No. 71 of 2019 concerning the Implementation of Electronic Systems and Transactions (PSTE) in combating ransomware crimes in Indonesia. The ever-evolving ransomware threat has triggered the need for regulations capable of adaptively responding to the dynamics of cybercrime. This study uses a normative juridical method with a qualitative approach to examine the urgency of implementation and obstacles in its implementation. The study results indicate that PP No. 71 of 2019 still faces various challenges, such as weak technical understanding, minimal coordination between agencies, limited legal sanctions, and a lack of technical guidance for prevention and mitigation. This study's recommendations include the development of detailed technical guidelines, strengthening the role of the National Cyber ​​and Crypto Agency (BSSN), digital security education, and harmonization with the Personal Data Protection Law. A comprehensive and collaborative legal strategy is needed to build national cyber resilience in the face of ransomware threats.